DEVELOPMENT OF PETUALANGAN DODU MEDIA TO IMPROVE STATISTICS LEARNING OUTCOMES IN ELEMENTARY SCHOOL GRADE V - Ervita Triani; Ira Rengganis; Rosiana Mufliva (Universitas Majalengka, 2024)
This research aims to develop the Dodu Adventure media to improve learning outcomes in statistics for fifth-grade elementary school students. The objective is motivated by several factors: 1) Students' abilities to understand statistics vary; 2) Statistics is abstract so students require guidance, repetition, and visualization; 3) Teaching generally uses conventional methods, where teachers explain and provide practice problems. These issues lead to a lack of enthusiasm during the learning process and an uneven understanding of statistical material, resulting in generally low learning outcomes. The method used in this research is the Design and Development (D&D) method, developed using the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. The development of the Dodu Adventure media is based on learning outcomes and the scope of the statistics curriculum for fifth-grade students. The first material validation results showed the Dodu Adventure media received a score of 88.9%, categorized as very suitable and considered suitable with revisions. In the second material validation, the media scored 98.1%, considered suitable without revisions by material experts. In media validation, Dodu Adventure received a score of 93.5%, categorized as very suitable and considered suitable with revisions by media experts. Lastly, in learning validation, the learning experts gave a score of 89.5%, considered suitable without revisions. Additionally, based on pre-test and post-test results from 26 students at SDN 053 Cisitu, data showed improvement. The average pre-test score was 52.1, while the post-test score was 72.6. The N-gain result was 0.46, categorized as a moderate improvement.